2014
DOI: 10.1074/mcp.m113.035667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Factors Involved in Type 1 Fimbria Expression using an Escherichia coli K12 Proteome Chip

Abstract: Type 1 fimbriae are filamentous structures on Escherichia coli. These structures are important adherence factors. Because binding to the host cells is the first step of infection, type 1 fimbria is an important virulence factor of pathogenic E. coli. Expression of type 1 fimbria is regulated by a phase variation in which each individual bacterium can alternate between fimbriated (phase-ON) and nonfimbriated (phase-OFF) states. The phase variation is regulated by the flipping of the 314-bp fimS fragment, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…GI1 has 4,305 bp, encompassing seven genes, mainly of unknown function, while GI2 has 9,148 bp, comprising ten genes related to type 1 fimbrial assembly. Type 1 fimbriae are filamentous surface organelles that mediate bacterial adherence to biotic and abiotic surfaces [25]. Interestingly, E. bugandensis UENF-21GII possesses several other genes related to type 1 fimbrial assembly along its core and accessory genomes, suggesting that this unique horizontally-acquired fimbrial operon might play specific roles in this strain.…”
Section: Resultsmentioning
confidence: 99%
“…GI1 has 4,305 bp, encompassing seven genes, mainly of unknown function, while GI2 has 9,148 bp, comprising ten genes related to type 1 fimbrial assembly. Type 1 fimbriae are filamentous surface organelles that mediate bacterial adherence to biotic and abiotic surfaces [25]. Interestingly, E. bugandensis UENF-21GII possesses several other genes related to type 1 fimbrial assembly along its core and accessory genomes, suggesting that this unique horizontally-acquired fimbrial operon might play specific roles in this strain.…”
Section: Resultsmentioning
confidence: 99%
“…Type-1 fimbia is a well-known adherence factor of UPEC to bind to bladder epithelial cells during UTIs ( Kaper et al, 2004 ). It has been reported that in a neonatal meningitides E. coli strain RS218 spr deletion increases the ratio of the colonies containing Type 1 fimbria phase-ON cells when they are grown on agar plates, and that the crosstalk between the expression of Type 1 fimbria and flagella has been shown in E. coli strains ( Barnich et al, 2003 ; Lane et al, 2007b ; Chen et al, 2014 ). However, Spr deficiency may not affect the expression of Type 1 fimbria in the UPEC strain UTI89, because WT-UTI89 and ∆ spr -UTI89 showed similar levels of Type 1 fimbria phase-ON bacteria in the culture ( Supplementary Figure S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ycbS -lacking E. coli mutant was obtained from the Keio collection 41 . To complement the Keio ycbS mutants, the plasmid pCA24N–ycbS harbouring ycbS was obtained from the ASKA clone library 42 and used to transform the ycbS mutant, as previously described 47 .…”
Section: Methodsmentioning
confidence: 99%